The Effect of Al-Zn Composition and Immersion Time in The Galvalume Process on Low Carbon Steel Microstructure,Mechanical Properties, and Corrosion Rate - Muda, Iskandar; Pradoto Ambardi; Martijanti; Kiki Fadlurahman (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
The effect of Al-Zn composition and holding time on thickness, layer structure formation, mechanical properties, and corrosion resistance during the hot dip galvalume process on low-carbon steel has been carried out. Low-carbon steel is used with a chemical composition of 0.01-0.25% Carbon. The parameters used were Al55%-Zn45%, Al60%-Zn40%, and Al65%-Zn35%. The variations in immersion time used were 10 seconds, 20 seconds, and 30 seconds. The samples were tested, including Vickers micro testing, layer thickness, metallography with an optical microscope, Scanning Electron Microscope (SEM/EDS), X-ray diffraction (XRD), and dynamic potential testing. The highest layer hardness value obtained from the test results on the Al55%-Zn45% composition variation with a holding time of 30 seconds was 208.20 HV. The lowest layer hardness value obtained from the test results on the composition variation of Al65%-Zn35% with a holding time of 10 seconds is 172.16 HV. The lowest layer thickness value at a holding time of 10 seconds is 342.0 micrometers. The highest layer thickness value at a holding time of 30 seconds is 1358.0 micrometers. The range of corrosion rates is 2.097-4.69 mpy.